Calodium hepaticum (Nematoda: Capillariidae) in synanthropic rodents (Rattus norvegicus and Rattus rattus) in Eastern Amazonia - Moreira,Vera Lúcia Coimbra (2013)
Calodium hepaticum (syn. Capillaria hepatica) is a trichurid nematode that parasitizes the hepatic parenchyma of rodents and other mammals. Infections in humans are rare, although they have been reported worldwide. A number of factors contribute to the distribution of this zoonosis, particularly the presence of dense populations of rodents associated with relatively poor urban environments, such as those found in parts of the northern Brazilian city of Belém in the eastern Amazon Basin. This study quantifiedCalodium infections in commensal synanthropic rodents in Belém. Rodents were captured in three neighborhoods characterized by poor public sanitation and the city's highest incidence of human leptospirosis. A total of 50 rodents were captured (26 Rattus rattus and 24 R. norvegicus), and 23 (10 R. rattus and 13R. norvegicus) presented macroscopic lesions typical ofC. hepaticum. Light microscopy of fresh samples and histological specimens permitted the identification of larvae and adult specimens containing numerous eggs with a double-striated shell and bipolar opercula with plugs. This is the first report of C. hepaticumin R. rattus and R. norvegicus from the Amazon Basin, and it shows a considerable risk of transmission to the local human population.